UNDER NEW MANAGEMENT: SCHOOL MANAGEMENT IN SEARCH OF PARADIGMATIC CHANGE - Liberato Shibuta, Regina; Aparecida Behrens, Marilda (Revista Gênero e Interdisciplinaridade, 2023)
This article presents an observation that was accomplished with the support of the Pefop (Paradigmas Educacionais e Formação de Professores) research group, at a private Elementary school with the objective to analize the school management culture over the professional development of teachers focusing on the paradigm of complexity. It was defined as the research problem: how do school culture and its management leaders motivate and have impact on professional development of teachers and their pedagogical practices in Elementary school. In a qualitative approach, as a study case, in which twenty teachers were involved, the school principal and two coordinators. In the process, it was chosen to have semi-structured interviews, classes observations and follow-up report about the courses teachers are due to accomplish during the school year. We concluded that, teacher in elementary school have no knowledge about the paradigm of complexity although they present some pedagogical techniques that are related to such approach, even though they are subject to the traditional method of teaching but with the support and motivation from school leaders, they are able to keep improving each day and making the difference in their students´ lives.